PEMBERDAYAAN KELOMPOK TANI LUWAK HITAM DESA BANDUNG JAYA - Rita, Wismalinda; N. Hidayah; S. Ardiansyah; Neli Definiati; Rita Zurina; Parwito, Parwito; Susilo, Edi (Fakultas Pertanian, 2024)
Luak Hitam Farmer Group, one of twelve farmer groups in Bandung Jaya Village, has great potential in the plantation, agriculture, and poultry farming sectors. However, high fluctuations in the price of feed concentrates are an obstacle in meeting the nutritional needs of poultry. On the other hand, the abundance of durian seeds as a source of energy and gold snails as a source of feed for ducks in this area has not been optimally utilized. In addition, post-harvest processing of quail into high-economic value products has also not been done effectively. This community service program aims to increase the knowledge and skills of farmer groups in processing durian seeds and gold snails into feed ingredients and post-harvest processing of quail. Activities include program socialization, education, and training, as well as mentoring, monitoring, and evaluation. The results of the program showed an increase in the knowledge and skills of the Luak Hitam Farmer Group in producing alternative feed made from durian seed flour and gold snail, as well as post-harvest management of quail into products of economic value.